INTRINSIC FACTORS AND FIRM FINANCIAL ANALYSIS WITH TRIPPLE BOTTOM LINES AS INTERVENING VARIABLE AGAINST FIRM VALUE Empirical Studies on Property and Real Estate Companies Year 2010-2013 - Sari, Mia Andika; Wiralaga, Harya Kuncara; Warokka, Ari (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
This research conducted to examine the influence of intrinsic factors which being proxied with Capital Structure, Firm Size, Firm Age and Financial factors that being proxied with liquidity, profitability also with another activities using tripple bottom lines as Intervening Variable against Firm Value of Property Industries. The data that being used in this study were obtained from published financial statements during the period 2010 to 2013, as well as annual reports that can be accessed through the IDX website. Data analysis technique used in this study is a regression with panel data and path analysis. The results of this research showed that intrinsic factors and financial variables have a significant influence on the firm value, as well as intrinsic factors and financial variables have a significant influence on the tripple bottom lines. From the results of path analysis demonstrated that the indirect effect using the tripple bottom lines as a intervening variable was greater than the direct effect. Key word: Intrinsic Factors, Financial Factors, Firm Values, Tripple Bottom Line.